Oncological outcomes of sequential laparoscopic gastrectomy after treatment with camrelizumab combined with nab-paclitaxel plus S-1 for gastric cancer with serosal invasion - Lin, Ju-Li; Lin, Mi; Lin, Guang-Tan; Zhong, Qing; Lu, Jun; Zheng, Chao-Hui; Xie, Jian-Wei; Wang, Jia-bin; Huang, Chang-Ming; Li, Ping (Frontiers in Immunology, 2024)
Objective: To explore the oncological outcomes of sequential laparoscopic gastrectomy after treatment with camrelizumab in combination with nab-paclitaxel plus S-1 for the treatment of gastric cancer with serosal invasion.This study is a retrospective cohort study and retrospectively analyzed the clinicopathological data of 128 patients with serosal invasion gastric cancer (cT4NxM0) who received nab-paclitaxel + S-1(SAP) or camrelizumab + nab-paclitaxel + S-1 (C-SAP) regimen and underwent laparoscopy assisted gastrectomy in Fujian Union Hospital from March 2019 to December 2020. The patients were divided into SAP group and C-SAP group. The 2-years overall survival rate, 2-year recurrence free survival rate recurrence rate and initial recurrence time were compared between the two groups.Results: A total of 128 patients were included, including 90 cases in SAP group and 38 cases in C-SAP group. There were no significant differences in age, gender, gastrectomy method, surgical approach, R0 resection, nerve invasion, vascular invasion, total number of harvested lymph nodes, number of positive lymph nodes and major pathologic response (MPR) rate between the two groups (P>0.05).However, the proportion of ypT0, ypN0 and pCR rate in C-SAP group were significantly higher than those in SAP group (P<0.05). The 2-year OS of C-SAP group (80.7%) was higher than that of SAP group (67.8%), and the difference was not statistically significant (P = 0.112); At 2 years after operation, the recurrence rate of C-SAP group (44.3%) was lower than that of SAP group (55.8%) (P = 0.097); Further analysis showed that the average time to recurrence in the C-SAP group was 18.9 months, which was longer than that in SAP group 13.1 months (P = 0.004); The 2-year recurrence free survival rate in C-SAP group was higher than that in SAP group (P=0.076); There was no significant difference in the overall survival time after recurrence between the two groups ( P= 0.097).Camrelizumab combined with neoadjuvant chemotherapy can improve the proportion of ypT0, ypN0 and pCR in patients, while prolonging the initial recurrence time of patients in the C-SAP group, but did not increase the immunotherapy/chemotherapy related side effects and postoperative complications.